Karawitan Composition Benang Raja | Komposisi Karawitan Benang Raja - I Putu Yudik Setyawan; I Ketut Sudhana; I Nyoman Mariyana (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
Natural phenomena are unsystematic events in the physical view, and then created by humans. Natural phenomena can occur anywhere and anytime, sometimes even without being predicted in advance. Every phenomenon that exists can be beautiful, but it can also be dangerous, known as natural disasters. In Indonesia, there are several natural phenomena that have a negative impact on humans such as: volcanic eruptions, tsunamis, flash floods, tornadoes and so on. This phenomenon is very bad and detrimental to humans both in terms of health and not spared from an economic point of view. However, in contrast to natural phenomena that are beautiful or harmless. Natural phenomena that are not dangerous show more beauty, majesty, and make everyone stunned to see the phenomenon. These kinds of phenomena are aurora, solar eclipse, lunar eclipse, shooting star and one of them is rainbow. A rainbow is an optical phenomenon that occurs when sunlight and rain react in a certain way. This is caused by refraction of sunlight. This ray changes direction from traveling one medium to another by water droplets in the atmosphere. Rainbows can be full circles, but observers usually only see an arc formed by light droplets on the ground and centered on the line from the sun to the observer's eye. Then the colors that appear in the rainbow are beautiful colors known as mejikuhibiniu (Red, Orange, Yellow, Green, Blue, Indigo and Purple).